G237(P) Paediatric trauma at an adult major trauma centre: "the kids are all right". (27th April 2016) - Bevan, C; Lazner, M; Clarke, L
Abstract : Introduction: Major trauma is the leading cause of death and disability in children, however compared to adults, children represent a much smaller number. The Trauma Audit and Research Network (TARN) states that 65.8% of Paediatric Major Trauma does not initially present to a Children's Major Trauma Centre (MTC), however there is little research into the role of a Paediatric Trauma Unit (PTU) in the management of paediatric major trauma (PMT). Aim: To review all admitted paediatric trauma patients at a PTU, focussing on the management of PMT, to establish whether the PTU management of these patients was safe and comparable to recommended practice. Methods: A retrospective review of all trauma patients age <17 years that were admitted to or transferred from a PTU between 1 st August 2013 and 31 st July 2014. Results: 491 admitted trauma patients (TP) were identified. 8 (1.6%) were PMT. The majority of PMT (62.5%) were male, with a median age of 12 years. 66% of TP and 88% of PMT received a trauma call, with 70% of PMT presenting between 0900–2200 h. 50% PMT was transferred to a specialist treatment centre. 3 patients (2 head injuries and 1 significant liver injury) were transferred between 3–6 h after presentation and 1 patient with a spinal injury after 2 days. Only 50% of PMT had their data collected by TARN, having a mean ISS of 23. The 4 patients who were not transferred and were treated at the PTU had an ISS of 13–24. There was zero mortality in the study and there were no significant incidents or delays in definitive treatment identified. Conclusion: In our study, we found that management of PMT at a PTU was comparable to recommended practice. As it is difficult to identify PMT pre-hospital, it is essential that PTU develop robust services and provide trauma evaluation and initial management expertise equal to a Children's MTC. To support this we provide paediatric consultant presence between 0900–2400 h. Greater vigilance is also needed when collecting PMT data for TARN to contribute to national data collection and facilitate quality improvement.